2020
DOI: 10.1155/2020/8836771
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Varying Combination Ratios of A. cordifolia and M. indica against Field and Laboratory Strains of P. falciparum In Vitro

Abstract: Background. Drug resistance in malaria is a global problem, with reports of Plasmodium parasites resistant to the current first-line antimalarial drug, artemisinin, expanding from Southeast Asia to Africa. There is therefore an urgent need to identify new drug candidates that will be effective against the existing malaria parasites. Drug combination therapy presents a myriad of advantages over monotherapy including delayed onset of resistance, potentiation, and synergism. This present study explored the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…Plasmodium berghei strain was used in 25 studies while Plasmodium yoeli was reported that in a single study. Sixteen (16) of the 26 extracts tested present a good activity in vivo i.e. 61.54% of plants studied and among them, those from methanol and water distilled respectively have recorded more active plants with 5 plants each.…”
Section: Resultsmentioning
confidence: 97%
“…Plasmodium berghei strain was used in 25 studies while Plasmodium yoeli was reported that in a single study. Sixteen (16) of the 26 extracts tested present a good activity in vivo i.e. 61.54% of plants studied and among them, those from methanol and water distilled respectively have recorded more active plants with 5 plants each.…”
Section: Resultsmentioning
confidence: 97%
“…M. indica is grown in tropical regions around the world, including India, Thailand, China, Bangladesh, Malaysia and Indonesia (Pierson et al, 2014). M. indica aqueous extract exhibited IC 50 of 18.11, 20.08, and 10.23 μg/ml against NF54, CamWT_C580Y, and FA08 parasite strains of P. falciparum, respectively (Jibira et al, 2020).…”
Section: Anacardiaceaementioning
confidence: 99%